Boro total, disponível e características de sorção em solos do estado do Ceará - Silva, Mary Nice de Magalhães e (1984)
In samples of fifteen soils, collected at the 0-20 and 20-40cm depths and in four profiles, each one representing existing classes in the State of Ceará, have been evaluated in relation to the content of total and Available boron, and the results have been correlated with other soil physical and chemical properties. [...]